Unraveling the binding characteristics of small ligands to telomeric DNA by pressure modulation - Oliva, Rosario; Mukherjee, Sanjib; Winter, Roland (Technische Universität Dortmund, 2021)
Recently, non-canonical DNA structures, such as G-quadruplexes (GQs), were found to be highly pressure sensitive, suggesting that pressure modulation studies can provide additional mechanistic details of such biomolecular systems. Using FRET and CD spectroscopy as well as binding equilibrium measurements, we investigated the effect of pressure on the binding reaction of the ligand ThT to the quadruplex 22AG in solutions containing different ionic species and a crowding agent mimicking the intracellular milieu. Pressure modulation helped us to identify the different conformational substates adopted by the quadruplex at the different solution conditions and to determine the volumetric changes during complex formation and the conformational transitions involved. The magnitudes of the binding volumes are a hallmark of packing defects and hydrational changes upon ligand binding. The conformational substates of the GQ as well as the binding strength and the stoichiometry of complex formation depend strongly on the solution conditions as well as on pressure. High hydrostatic pressure can also impact GQs inside living cells and thus affect expression of genetic information in deep sea organisms. We show that sub-kbar pressures do not only affect the conformational dynamics and structures of GQs, but also their ligand binding reactions.
Scientific reports;11. 2021, Art. No. 9714
Keywords: Biophysics; Chemistry; 540